NET PROFIT MARGIN DAN CURRENT RATIO PENGARUHNYA TERHADAP HARGA SAHAM - ANDIKA PANJI DARMA SANATA; FRIYANTO (AKADEMIKA, 2022)
The purpose of this study is to find out and partially analyze the effect of Net Profit Margin (NPM) on stock prices of food & beverage sub-sector companies listed on the Indonesian stock exchange for the 2016-2018 period. The population used in this study is the Food & Beverages Sub-sector Manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 – 2018. In this study, 10 companies met the criteria as samples. The data used are secondary data obtained from the company's official website, the IDX's official website at www.idx.com. The type of research used in this research is explanatory research. The method used in this study is a quantitative method. The results of the t-test indicate that NPM and CR have a significant value below 0.05, which is 0.0001. This means that NPM and CR partially have a significant influence on stock prices.